Mallomonas loricata sp. nov. (Synurales, Chrysophyceae), a new tropical species from section Planae - Gusev, Evgeniy; Shkurina, Nataliya; Kulikovskiy, Maxim (Phytotaxa, 2021)
A new species, Mallomonas loricata sp. nov., is described from Vietnam based on silica-scale morphology studied using transmission and scanning electron microscopy. The species belongs to section Planae and has similar morphology to species from the Mallomonas matvienkoae complex. The new species is characterized by obovoid scales with a thick secondary layer with internal reticulation that covers almost whole surface of the scale. Scales of Mallomonas loricata were found at twenty-four localities of eight provinces in northern, central and southern areas of Vietnam. Scales of this new species have also been previously reported from Singapore and Malaysia. The distribution and habitat conditions of the new species are summarized.